Age and sex inequalities in the prescription of evidence-based pharmacological therapy following an acute coronary syndrome in Portugal: the EURHOBOP study. (November 2014) - Pereira, Marta; Araújo, Carla; Dias, Paula; Lunet, Nuno; Subirana, Isaac; Marrugat, Jaume; Capewell, Simon; Bennett, Kathleen; Azevedo, Ana
Aim: To assess the proportion of patients receiving pharmacological therapy for secondary prevention after an acute coronary syndrome (ACS) in Portugal and to identify age and sex inequalities. Design: Retrospective cohort study. Methods: We studied 747 episodes of ST-segment elevation myocardial infarction (STEMI) and 1364 of non-ST-segment elevation ACS (NSTE-ACS), within a sample of ACS cases consecutively discharged from 10 Portuguese hospitals, in 2008–2009. We estimated adjusted odds ratios (OR) for the association of age and sex with the use of each pharmacological treatment. Results: In STEMI and NSTE-ACS patients, the proportion of patients discharged with aspirin was 96 and 88%, clopidogrel 91 and 78%, aspirin+clopidogrel 88 and 71%, beta-blockers 80 and 76%, angiotensin-converting enzyme (ACE) inhibitors/ARB 82 and 80%, statins 93 and 90%, 3-drug (aspirin/clopidogrel+beta-blocker+statin) 76 and 69%, and 5-drug treatment (aspirin+clopidogrel+beta-blocker+ACE inhibitor/ARB+statin) 61 and 48%, respectively. Among STEMI patients, those aged ≥80 years were substantially less often discharged with clopidogrel (OR 0.22, 95% confidence interval, CI, 0.08–0.56), aspirin+clopidogrel (OR 0.34, 95% CI 0.15–0.76), beta-blockers (OR 0.39, 95% CI 0.18–0.82), 3-drug (OR 0.41, 95% CI 0.21–0.83), and 5-drug treatments (OR 0.44, 95% CI 0.23–0.83) than those <60 years; women were less likely to be discharged with aspirin+clopidogrel (OR 0.52, 95% CI 0.29–0.91). Among NSTE-ACS patients, those aged ≥80 years were much less likely to be discharged with beta-blockers (OR 0.58, 95% CI 0.36–0.93), statins (OR 0.35, 95% CI 0.19–0.64), and 3-drug treatment (OR 0.47, 95% CI 0.30–0.75); sex had no significant effect on treatment prescription. Conclusions: The vast majority of younger patients were discharged on evidence-based secondary preventive medications, but only half received the 5-drug combination. Recommended therapies were substantially underprescribed in older patients.